Oxygen transfer in cell-free and simulated alkane-based bioprocesses : Computational Fluid Dynamics (CFD) simulations and predictive modelling - Gakingo, Godfrey Kabungo (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.